Upaya Pemerintah Desa Dalam Meningkatkan Pemberdayaan Ekonomi Masyarakat Nelayan Desa Nen Bura Kecamatan Doreng Kabupaten Sikka - Fransiskus Hendro; Mohammad Taufik Arifin; Mohammad Amir (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
."Village Government Efforts to Increase the Economic Empowerment of the Fishing Community of Nen Bura Village, Sikka Regency". Thesis. Maumere: Faculty of Social Sciences and Humanities Education IKIP Muhammadiyah Maumere, 2023. The aim of this research is to determine the village government's efforts to improve the economy of the fishing community in Nenbura village, Doreng sub-district, Sikka district AND the village government's obstacles in improving the economy of the fishing community in Nen Bura village, Doreng sub-district, Sikka district. In this research the method used is descriptive qualitative, with techniques collecting observation data, interviews and documentation. The data analysis techniques used are data reduction, data display and conclusion drawing. with the results of research on government efforts to empower fishing communities in Nen Bura Village. The government in Nen Bura village has effectively carried out its duties as government, especially in collaboration with the Department of Fisheries and Maritime Affairs, where the government has provided sufficient assistance to the fishing community in Nen Bura Village, such as machines, boats and fishing nets, but not all fishing communities receive this assistance. Obstacles to Government Efforts in Empowering Fisher Community Budget limitations are one of the important factors in implementing the empowerment program in Nen Bura Village. Because the budget is a driving factor for the smooth running of all elements of government institutions. Budget limitations are a fundamental problem or the empowerment program cannot run well and does not meet the needs of fishermen. So the government is still trying as hard as possible to prepare the needs so that the empowerment implementation program can run well.